The Translation Shift Analysis of Nominal Groups in The Martian Movie Subtitle - Mia Putri Meidha (Passage, 2017)
This research aims to analyze the translation shifts of nominal groups that occur in The Martian movie subtitle, and investigates how the translation shifts affect meanings. This study employs a qualitative descriptive method as proposed by Cresswell (2007). The data of this study are taken from the movie transcriptions and subtitle in The Martian (2015) movie. The data are analyzed by using Gerot and Wignell’s (1994) theory of nominal groups and Catford’s (1965) category of translation shifts which include structure shift, class shift, unit shift, and intra-system shift. The analysis shows that the process of translating involves single and double translation shifts. In single translation shift, structure shift is the most dominant translation shift (75,7%). In double translation shift, the most dominant shift is the combination of structure and intra-system shift (12,6%). The analysis also shows that the translation process involves the combination of unit and intra-system shift (0,8%), and the combination of class and unit shift (0,3%). The translation shifts are found affecting meanings. There are 37 nominal groups which experience changes in meanings due to the translation shift strategy. The implication of the study relates to the significance of understanding linguistic features as a choice to convey certain meanings in another language.Keywords: Translation Shifts, Nominal Groups, meaning shifts, subtitle